Perinatal Exposure of Bisphenol A Differently Affects Dendritic Spines of Male and Female Grown-Up Adult Hippocampal Neurons - Kawato, Suguru; Ogiue-Ikeda, Mari; Soma, Mika; Yoshino, Hinako; Kominami, Toshihiro; Saito, Minoru; Aou, Shuji; Hojo, Yasushi (Frontiers in Neuroscience, 2021)
Perinatal exposure to Bisphenol A (BPA) at very low dose may modulate the development of synapses of the hippocampus during growing up to adult. Here, we demonstrated that perinatal exposure to 30 μg BPA/kg mother body weight/day significantly altered the dendritic spines of the grownup rat hippocampus. The density of spine was analyzed by imaging of Lucifer Yellow-injected CA1 glutamatergic neurons in adult hippocampal slices. In offspring 3-month male hippocampus, the total spine density was significantly decreased by BPA exposure from 2.26 spines/μm (control, no BPA exposure) to 1.96 spines/μm (BPA exposure). In offspring 3-month female hippocampus, the total spine density was significantly increased at Estrus stage (2.25 spines/μm), but only moderately decreased at Proestrus stage (2.19 spines/μm). Thus, after the perinatal exposure to BPA, the total spine density in male became lower than that in female. Concerning the BPA effect on the morphology of spines, the large-head spine was significantly changed, with its significant decrease in male and moderate change in female. Interestingly, BPA exposure considerably changed the normal 4-day estrus cycle, resulting in a 5-day estrus cycle with 2 day estrus stages in many subjects. Since specific BPA receptor ERRγ (estrogen receptor related protein gamma) is localized in hippocampal CA1 neurons, ERRγ may contribute to the observed BPA effects.